Fine-tuning the CAR spacer improves T-cell potency. (1st December 2016) - Watanabe, Norihiro; Bajgain, Pradip; Sukumaran, Sujita; Ansari, Salma; Heslop, Helen E.; Rooney, Cliona M.; Brenner, Malcolm K.; Leen, Ann M.; Vera, Juan F.
ABSTRACT: The adoptive transfer of genetically engineered T cells expressing chimeric antigen receptors (CARs) has emerged as a transformative cancer therapy with curative potential, precipitating a wave of preclinical and clinical studies in academic centers and the private sector. Indeed, significant effort has been devoted to improving clinical benefit by incorporating accessory genes/CAR endodomains designed to enhance cellular migration, promote in vivo expansion/persistence or enhance safety by genetic programming to enable the recognition of a tumor signature. However, our efforts centered on exploring whether CAR T-cell potency could be enhanced by modifying pre-existing CAR components. We now demonstrate how molecular refinements to the CAR spacer can impact multiple biological processes including tonic signaling, cell aging, tumor localization, and antigen recognition, culminating in superior in vivo antitumor activity.